The performance of Felda Plantations Sdn. Bhd. contractors - Ibrahim, Ramzi (2006)
Performance is the measure of the ability of the contractors to execute work on time, cost and quality. This study presents the result of the investigation on performance of the contractor that registered under Felda Plantations Sdn. Bhd based on workmanship. The objectives of the study are to identify the factors that influence the contractor’s performance; to establish the critical factors that influence their performance; and to identify the strategies to improve the situation. The method of the study involved literature review, data collection and analysis is using an Average Index method. The result for this study is found that the three most important factors that influence the contractors performance were the experience and skilled worker; understand the method of work; and good planning and scheduling . The three best method to improve the contractor’s performance were to focus on the client needs; meet the client requirements; and exceed the client expectation; to improve the method of supervision of labors work and to improve the planning and scheduling techniques. It is hope that this study will provide useful information on future work for contractors not only for their future jobs at Felda Plantations Sdn. Bhd. but to the benefit to the construction industry